Detection of Hepatitis E Virus in Hyalomma lusitanicum Ticks Feeding on Wild Boars - Rivero-Juarez, Antonio; Risalde, María A.; Gortázar, Christian; Lopez-Lopez, Pedro; Barasona, Jose A.; Frias, Mario; Caballero-Gomez, Javier; de la Fuente, José; Rivero, Antonio (Frontiers in Microbiology, 2021)
Little is known about the role of ticks in maintaining highly prevalent zoonotic viruses in wildlife, such as hepatitis E virus, that do not require ticks for transmission between animals and humans. In this cross-sectional study, adult female ticks were collected from Eurasian wild boar (Sus scrofa) in autumn 2015 in Spain. HEV RNA in both ticks and wild boar was evaluated by RT-qPCR. Twenty-nine adult Hyalomma lusitanicum ticks were collected from 29 wild boar. HEV RNA was detected in a total of ten ticks (34.4%) and 11 wild boar serum samples (37.9%). In two cases, detectable HEV RNA was found in a wild boar but not in the tick collected from them. In contrast, one HEV-positive tick was collected from an HEV-negative wild boar. All viral sequences were consistent with genotype 3f. We describe for the first time the presence of HEV RNA in adult Hyalomma lusitanicum ticks.